Mentor teachers’ perspectives on the preparedness of student teachers to teach business studies during teaching practice - Nduduzo Brian Gcabashe (Perspectives in Education)
Business studies student teachers are expected to showcase different knowledge domains during teaching practice, including their pedagogical and content knowledge. Student teachers teach under the guidance of mentor teachers. Given the crucial role that mentor teachers play, this qualitative study explores the views of mentor teachers on the preparedness of business studies student teachers to teach. Situated learning theory was adopted as the theoretical lens of this study. A systematic random sampling technique selected seventeen e-portfolios submitted by third year student teachers after engaging in teaching practice. Mentor teachers’ reports were analysed using an e-portfolio evaluation tool that the researcher developed. Mentor teachers’ contributions were recorded in the spreadsheet to generate data, and thematic analysis was used to analyse the data. The study revealed that some mentor teachers were satisfied with student teachers’ content and pedagogical knowledge. However, there are crucial areas where student teachers need to improve. Based on the findings, this study recommended that teacher educators strengthen their business studies methodology module content and assessments to equip student teachers with classroom management and time management skills.